A Pilot Study Examining Body Composition Classification Differences Between Body Mass Index and Bioelectrical Impedance Analysis in Children With High Levels of Physical Activity - David J. Farbo (Frontiers Media S.A., 2021)
Background: Body mass index (BMI) is frequently labeled as “flawed” in assessing obesity since it cannot differentiate between muscle and fat leading to misclassifications of healthy individuals. Bioelectrical impedance analysis (BIA) may be a more accurate indicator of obesity since it can distinguish the difference between muscle and fat in children. This pilot study investigated discrepancies between BMI and BIA body composition classifications in children with high levels of physical activity.Methods: Participants were selected from three elementary schools (N = 380, K = 76, 1st = 64, 2nd = 62, 3rd = 61, 4th = 83, and 5th = 34) receiving 60 min of outdoor, unstructured play daily. BIA scales were used to collect each child's body fat percentage and BMI score, then those numbers were categorized by BIA and BMI normative values as either underweight, healthy, overweight, or obese.Results: Overall, 26% of the students were classified differently when using the normative classifications for BMI and BIA, with the largest discrepancy found in the overweight category at 38%. Similar inconsistencies were found when students were divided as younger (42%) vs older students (36%), and males (40%) vs. females (35%).Conclusions: This pilot study demonstrated that there is a significant difference in how BMI and BIA discriminate between the different body composition categories. BIA consistently shows to be a more accurate tool in assessing obesity rates in children since it directly measures body fat.